E-learning readiness among dental students and faculty: a comparative study before and after the COVID-19 pandemic - Zahid, Talal M.; Agou, Shoroog (Frontiers in Medicine, 2024)
The COVID-19 pandemic accelerated the global adoption of e-learning, even in institutions that had previous reservations. Nevertheless, the impact of this transformation on dental education remain unclear. This study aimed to assess the e-learning readiness of dental students and faculty before and after COVID-19. It also explored their post-pandemic e-learning preferences for dental education.Methods: Cross-sectional surveys were conducted at King Abdulaziz University's Faculty of Dentistry (KAUFD) in Jeddah, Saudi Arabia both before and after COVID-19. Faculty and students from two distinct cohorts were recruited at two time points. Participants completed a detailed questionnaire on e-learning readiness across multiple domains. Statistical analysis was performed using R v 3.6.3. Descriptive and group comparisons were conducted using chisquared test, unpaired t-test, and Spearman's correlation.Results: 1057 responses (response rate = 99.8%) were analyzed: 2015 (n = 400) and 2021 (n = 657). Both faculty and students demonstrated significant improvements in e-learning readiness across all domains from 2015 to 2021. In 2021, faculty members scored significantly higher than students in almost all readiness domains, except for e-learning experience (p <0.001 for all domains). After the pandemic, both groups preferred a blended learning model: 75% traditional and 25% online education. A significant increase in typing and editing training requests by faculty and students was observed in 2021. Students showed a decline in training needs for web and online tool usage.The COVID-19 pandemic pushed the rapid adoption of e-learning in dental education. In this study, faculty showed greater e-learning readiness, but students voiced concerns about missed in-person interactions, social isolation, and screen fatigue. Further multiinstitutional studies are required for more comprehensive insights.